IPA 203 A Promising Variety of long-duration pigeonpea - Choudhary, A. K. (Indian Farming, 2016)
In the NEPZ, area under pigeonpea has considerably declined partly because of the lack of highyielding FW resistant varieties with suitable plant types that could be inter-cropped with tall cereals such as maize, sorghum, pearl millets, etc. ‘IPA 203’ may be an ideal pigeonpea variety for this zone as it has high yield potential, compact plant type with multiple disease resistance. Empirical observation indicates that it also carries some degree of low temperature tolerance similar to one of its progenitors ‘Bahar’. Its rapid growth rate especially during early seedling stage helps it compete with rainy season annual weeds. Based on the recommendation of the VIC, the Central Sub-Committee on Crop Standards, Notification and Release of Varieties in Agricultural Crops, in its 72 nd Meeting on June 25, 2015 made recommendation for the release/notification of ‘IPA 203’(Prakash) for cultivation in the NEPZ of India.